ARTIFICIAL INTELLIGENCE AND LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the evolving relationship between artificial intelligence (AI) and language, exploring both the opportunities and challenges presented by AI's increasing role in communication and linguistic processing. It delves into key areas of AI language applications, including machine translation, natural language processing, and the development of large language models. The article also addresses crucial ethical considerations, such as algorithmic bias and the potential for misuse of AI-generated content, providing a balanced perspective on this transformative technological advancement. Researchers and practitioners in AI, linguistics, and related fields will find this analysis insightful and relevant.